Redefining space in immersive films: narrative fiction 360º videos - Barbera Hernández, Víctor Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
Immersive films are a new storytelling format that uses the image space as an essential audiovisual element to properly understand the narrative. We have conducted a content analysis on a sample composed of 360º narrative fiction videos, to which we applied a model composed of variables related to the organization of the space around the viewer. The results point to a centripetal organizational scheme, similar to immersive theater, where priority is given to the understanding of the main narrative over a true utilization of the space provided by this new format for storytelling.